Efektivitas Komunikasi Organisasi dalam Pelayanan Publik di Desa Parigi Tahun 2024 - Maulana, Jaka; Duandika, Reyhansa (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
Organizational communication plays a crucial role in enhancing the effectiveness of public services by ensuring that information about policies and services is well received and understood by the community. This study analyzes the effectiveness of organizational communication in public services in Parigi Village using Hardjana’s (2000) model, which includes six key indicators: Receiver, Content, Communication Media, Message Format, Source, and Timing. A quantitative descriptive approach was employed, with data collected through questionnaires distributed to 100 respondents who accessed public services in the last six months. The results show that Source scored the highest (61%), indicating strong public trust in the local government as a credible information provider, whereas Receiver scored the lowest (58%), highlighting challenges in understanding information due to literacy disparities and limited policy socialization. Additionally, Timing (60%) suggests that delays in delivering information, particularly concerning social assistance registration and administrative regulation changes, remain a challenge. The effectiveness of organizational communication influences the reliability and responsiveness of public services, with limitations in digital communication media being a major obstacle to improving transparency and information accessibility. Therefore, simplifying messages, optimizing digital media use, improving the timeliness of information delivery, and strengthening feedback mechanisms are essential strategies to enhance organizational communication and improve public satisfaction with services in Parigi Village.